2018
DOI: 10.1002/1878-0261.12362
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control of the CXCR7/CXCL11 chemokine axis by estrogen receptor α in ovarian cancer

Abstract: Ovarian cancer (OC) is one of the most intractable diseases, exhibiting tremendous molecular heterogeneity and lacking reliable methods for screening, resulting in late diagnosis and widespread peritoneal dissemination. Menopausal estrogen replacement therapy is a well‐recognized risk factor for OC, but little is known about how estrogen might contribute to this disease at the cellular level. This study identifies chemokine receptor CXCR7/ACKR3 as an estrogen‐responsive gene, whose expression is markedly enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 61 publications
0
28
0
1
Order By: Relevance
“…It was also found that higher levels of CXCL12(5-67) in brain were associated with HIV-1 infection (McQuibban, et al, 2001;Zhang, et al, 2003). The interesting and relevant part, is that this form of cleaved CXCL12(5-67) did not act through CXCR4, the regular receptor for intact CXCL12, but exerted its neurotoxic and immunogenic actions through the chemokine receptor CXCR3, which also shares the ligand CXCL11 with ACKR3, which is promiscuous in being activation-prone by Nterminal modified CXCL11 and CXCL12 (Benhadjeba, et al, 2018;Vergote, et al, 2006). This does not mean that DPP4-cleaved CXCL12 acts through CXCR3, but it reinforces the idea that a proteolytic enzyme can generate a new cryptic ligand to a receptor that was not activated by the intact parent peptide.…”
Section: Cxcl12 Effect On Brain and Nervous Systemmentioning
confidence: 99%
“…It was also found that higher levels of CXCL12(5-67) in brain were associated with HIV-1 infection (McQuibban, et al, 2001;Zhang, et al, 2003). The interesting and relevant part, is that this form of cleaved CXCL12(5-67) did not act through CXCR4, the regular receptor for intact CXCL12, but exerted its neurotoxic and immunogenic actions through the chemokine receptor CXCR3, which also shares the ligand CXCL11 with ACKR3, which is promiscuous in being activation-prone by Nterminal modified CXCL11 and CXCL12 (Benhadjeba, et al, 2018;Vergote, et al, 2006). This does not mean that DPP4-cleaved CXCL12 acts through CXCR3, but it reinforces the idea that a proteolytic enzyme can generate a new cryptic ligand to a receptor that was not activated by the intact parent peptide.…”
Section: Cxcl12 Effect On Brain and Nervous Systemmentioning
confidence: 99%
“…Moreover, it has been observed that CXCR7 (C-X-C Chemokine Receptor Type 7) and CXCL11 (C-X-C motif chemokine 11) genes are activated by estrogens through the direct recruitment of ERα and this leads to increased migration and invasion of OC cells [ 83 ]. Estrogens are also able to influence the anoikis process by Bit1 involvement.…”
Section: The Role Of Estrogen Receptors In Ovarian Cancermentioning
confidence: 99%
“…In fact, GWAS have identified several risk loci demonstrating a shared association between breast and ovarian cancer risk [19]. Previous studies have also shown that ESR1 is involved in the development and progression of EOC [30], and genetic susceptibility studies have suggested that polymorphisms in the ER-α gene confer increased risk for EOC [31]. Thus, in line with the present study, it is possible that the association between rs237028 and EOC susceptibility be mediated through the ER signaling pathway.…”
Section: Discussionmentioning
confidence: 99%